Contribution of the institute of metallurgy and ore beneficiation in organization of production of Rhenium and Osmium-187 isotope in Kazakhstan - Z. S. Abisheva; A. N. Zagorodnyaya (Тонкие химические технологии)
In the territory of Kazakhstan there are unique deposits, in which, along with non-ferrous metals, there are also other very valuable metals such as rhenium and isotope osmium-187. Kazakhstan is one of the leaders in the world in the production of ammonium perrhenate. This article is dedicated to the evolution in the organization of the production of rhenium compounds from various technogenic products resulting during processing of substandard molybdenum, copper, and lead concentrates and solutions of underground leaching of uranium ores for the production of the target metals. The first production of rhenium salts was organized in 1946 from dust resulting after oxidative roasting of sub-standard molybdenite concentrate. Later washing sulfuric acid of copper production and solutions from leaching of dusts of lead dust production were involved into the production of ammonium perrhenate. Data on the distribution of rhenium in these industries are given with the determination of rhenium in the gas phase by the technique developed by researchers of "Center of the Earth Sciences, Metallurgy and Ore Benificiation" (“CESMOB”). The flow sheets of implemented and adopted to implementation technologies of rhenium recovery from solid and liquid products elaborated by “CESMOB" are given in the article. Basic processes for the recovery of rhenium from the initial solutions are sorption and solvent extraction. For the recovery of rhenium from mother liquors obtained in the sorption and extraction technologies precipitation of rhenium in the form of complex salt [Zn(NH3)4](ReO4)2 was used.